An implementation of a student centred-approach in Atenas Primary School in Ambato. - Naranjo Holguín, María Paula (2001)
1. Child acquisitionof a second languaje 2. Multiple intelligences and learning styles 3. A student-centred approach 4. Becoming a student-centred teacher 5. The student-centresd classroom 6. Preliminary obsevation 7. Description of the application of the student-centred approach based on student's learning styles 8. Observation and analysis of the results of the application of the student-centres approach 9. Final results of the application of the student-centred approach in Atenas School 10. Bibliography